Subjects of forming the constitutional and legal policy in the field of human rights - Kolodiy , Anatolii; Ternavska , Viktoriia (Actual problems of law (Aktual'ni problemi pravoznavstva), 2026)
The priority direction of the constitutional and legal policy of the state is the establishment, provision and guarantee of human and citizen rights and freedoms at the legislative level. However, law-implementing practice demonstrates the existing formal and legal shortcomings of the current legislation and the declarative nature of the provisions of the current Constitution of Ukraine. The problem of efficiency of law-implementing practice is mostly caused by not always high-quality content of legal policy, which is mediated by the systematic and coordinated activity of the subjects of forming the constitutional and legal policy in the field of human rights. Taking this into account, the purpose of this study is to identify the participants of lawmaking activity who directly form the constitutional and legal policy in the field of human rights. There applied the provisions of the dialectical approach, methods of systemic-structural, deduction and induction, analysis and synthesis, the combined use of which made it possible to formulate the main boundaries of the study of the issue, as well as to carry out an appropriate search for ideas and conclusions regarding the features of constitutional and legal policy in the field of human rights and the subjects of its formation.Based on the analysis of doctrinal and normative sources, the authors conclude that constitutional and legal policy in the field of human rights is the activity of state authorities and local self-government bodies to produce legal ideas of a strategic nature by the participation of civil society institutions, which are embodied in legal acts aimed at improving the mechanism of constitutional and legal regulation and protection of social relations in the field of human rights. Systematic, coordinated activity of subjects of forming the constitutional and legal policy in the field of human rights is the key to the quality of this policy and the efficiency of law-implementing practice.